2019
DOI: 10.1093/neuros/nyz201
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Transnasal Trans-Sphenoidal Approach for Pituitary Adenomas: A Comparison to the Microscopic Approach Cohort by Propensity Score Analysis

Abstract: BACKGROUND Despite some evidence for the adoption of endoscopic transnasal trans-sphenoidal surgery (ETSS) for pituitary adenomas, the advantages of this technique over the traditional approach have not been robustly confirmed. OBJECTIVE To compare ETSS with the microscopic sublabial trans-septal trans-sphenoidal surgery (MTSS) for pituitary adenomas. METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 49 publications
3
25
3
Order By: Relevance
“…2%. [22][23][24][25][26][28][29][30][31][32][33][35][36][37][38][39][40][41][42][43]50 The rate of recovery from hormonal deficits in our study is greater than that found by other researchers. Most of our patients (83.9%) showed stable or improved hormonal deficits.…”
Section: Perioperative Outcomescontrasting
confidence: 65%
See 4 more Smart Citations
“…2%. [22][23][24][25][26][28][29][30][31][32][33][35][36][37][38][39][40][41][42][43]50 The rate of recovery from hormonal deficits in our study is greater than that found by other researchers. Most of our patients (83.9%) showed stable or improved hormonal deficits.…”
Section: Perioperative Outcomescontrasting
confidence: 65%
“…Other studies have reported rates of vision improvement from as low as 23% to as high as 100%. [22][23][24][25][26][28][29][30][31][32][33][34][37][38][39][40][41][42][43]50 In our study, no patients had worsened vision after surgery. This is consistent with results found by other researchers who generally saw a very low rate of worsened visual deficits after surgery, on the order of 0%e3.…”
Section: Perioperative Outcomessupporting
confidence: 40%
See 3 more Smart Citations